Dimension-reduction MUSIC for jointly estimating DOA and polarization using plane polarized arrays - Wei-jian SI; Tong ZHU; Meng-ying ZHANG (Tongxin xuebao)
Based on the long-vector data modal of polarization sensitive array,a joint estimation of DOA and polarization information algorithm suitable for plane polarized antenna arrays was proposed.Using the condition of partial derivative of spectral function to reduce the dimensionality,the computation significantly was decreased but also guarantees the resolution and estimation accuracy.Simulation results show that the proposed algorithm has better resolution and lower square mean compared to the effective Quaternion-MUSIC algorithm,and reduces computation of estimation.